Impact of initialization of a modified particle swarm optimization on cooperative source searching - Mad Helmi Ab. Majid, Abu Bakar Ibrahim (Tanjung Malim, 2024)
Impact of initialization of a modified particle swarm optimization on cooperative source searching by Mad Helmi Ab. Majid, Abu Bakar Ibrahim